Deep undercover - Worth, Lenora (True blue K-9 unit., 2019)
To take down a serial bomber, NYPD K-9 officers Brianne Hayes and Gavin Sutherland must go undercover--as a married couple. But now the bomber is targeting them to halt the investigation. As the clock ticks down, can Brianne, Gavin and their K-9 partners find the culprit in time to save the city--and their own lives?